PMP® certification training. (Packt Publishing, 2022)
Learn project management in the most effective and easy way, through this course. About This Video Understand the latest trends and emerging practices in PMP Learn the core competencies that are required by a project management professional Understand various case studies created by PMP-certified veterans In Detail Any project is bound to meet obstacles if the scope of the project is not identified correctly before the project commences. This course teaches you the best practices to identify the scope correctly and manage schedules, such that your project does not overshoot its costs. The course covers basic to advanced concepts, from an introduction to PMP and PMI, project management framework, project management processes groups, and role of the project to integration, scope, and schedule management. Some interesting topics from procurement management to stakeholder management have also been covered in detail. The course dives deeply into the concepts of professional and social responsibility and concludes by covering Agile concepts. By the end of this course, you will be able to work on any project and move the project toward completion. Audience This course is for beginners who want to start their career in project management and for practitioners who want to get PMP-certified. You should have a four-year degree with 4,500 hours of leading and directing projects along with 35 hours of project management education to start with the PMP course.